Exploration Of Rice Plant Endophyte Bacteria To Suppress Xanthomonas oryzae Bacterial Leaf Blight Disease - Ratih Nadhila Putri; Yenny Wuryandari; Endang Tri Wahyu (Universitas Labuhanbatu, 2025)
Background: Rice is a major food commodity for Indonesian. According to BPS (2022) rice production in 2021 decreased 0.43%. The decline caused by various factors, one of which is bacterial leaf blight disease by the pathogenic bacteria Xanthomonas oryzae. Control of X. oryzae mostly uses pesticides, but this control has a negative impact on the environment, therefore it is necessary to develop endophytic bacteria (EB) that can inhibit the growth of X. oryzae and can act as PGPR. This study was to determine the EB ability in healthy rice stem tissue to suppress bacterial leaf blight disease caused by the bacteria X. oryzae. Methodology: This research was were used isolation from infected plant for X. oryzae and from healthy plant for EB, data was analyzed using the corresponding formula. Findings: found 10 isolates of EB that could inhibit the X. oryzae growth as seen from the inhibition zone produced in the antagonist test. The EB isolates produced the largest inhibition zones such as BE18 (23.3 mm, very strong category), BE16 (13.3 mm, strong category), and BE3 (11.6 mm, strong category). The 4 isolates with bactericidal inhibition mechanisms, namely isolates (BE11, BE15, BE16, and BE18), 6 isolates with bacteriostatic inhibition mechanisms, namely isolates (BE3, BE5, BE6, BE7, BE12, and BE13). Contribution: The availability of EB present in the tissues of healthy rice stems is still relatively high and can be used to suppress the growth of pathogenic bacterium X. oryzae. This rseult also supported by the beneficial properties of EB, which can enhance plant resistance